EDUCATION ON THE EFFICACY OF THE CATHARANTUS ROSEUS PLANT AS A MOSQUITO REPELLENT - Aji, Rustam; Setyawan, Dodiet Aditya; Rachmat, Nur; Sulistiyani, Sulistiyani; Noorma, Nilam; Handayani, Tri; Fahlevi, Reza; Masdeniati, Masdeniati; Aji, Sherly Ratih Frichesyarius Santi; Ayuningtyas, Roro Aji (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
In the transition weather, the mosquito population is increasing. The Catharanthus roseus plant grows abundantly, which contains alkaloids, saponins, tannins and flavonoids which have the potential as larvicides and mosquito repellents, is one of the traditional medicinal plants used by the community. The aim of community service activities, students understand and are able to explain again. When the education was given, there were 22 students of Class VI B.SDN.07 Rejang Lebong, 99% of students were able to explain again about the properties of the Catharantus roseus plant as a mosquito repellent, 1 (one) 1% of students did not go to school .